PENGEMBANGAN BUKU CERITA INTERAKTIF BERBASIS MODEL PEMBELAJARAN PROJECT BASED LEARNING TERHADAP NILAI KARAKTER SOPAN SANTUN ANAK (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop interactive storybook media based on the Project Based Learning (PjBL) learning model as an effort to instill the character values ​​of politeness in children aged 5-6 years. The study used the Research and Development (R&D) method with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The subjects of the study were children aged 5-6 years at Sunan Ampel Kindergarten, Drancang Village, Menganti. Data collection techniques were carried out through validation sheets from material experts and media experts, teacher practicality questionnaires, as well as observations and tests to measure the effectiveness of the media. The results showed that the interactive storybook media based on the Project Based Learning learning model was declared very feasible to use with a percentage of material expert validation of 100% and media expert validation of 97.72%. The effectiveness of the media was proven through the results of the Wilcoxon Signed Rank Test which showed a significant increase in the character values ​​of children's politeness between the pretest and posttest results with a significance value of <0.05. The practicality of the media was assessed in the good to very good category with a Cronbach's Alpha value of 0.600 indicating a reliable instrument. Thus, interactive storybook media based on Project Based Learning is declared suitable, effective, and practical to be used as a learning medium to instill the character values ​​of politeness in children aged 5-6 years.